Treatment experience in managing severe immune-mediated hepatotoxicity induced by immune checkpoint inhibitors - Cao, Ruijie; Zhang, Shasha; Zhang, Jingjing; Zhao, Yufei; Zhang, Xiaoyun; Guo, Zhanjun (Frontiers in Oncology, 2025)
BackgroundAlthough multiple guidelines for managing severe immune-mediated hepatotoxicity (IMH) induced by immune checkpoint inhibitors (ICIs) were recommended, real-world research data regarding its clinical progression, treatment modalities, and outcomes remain scarce.MethodsThis study was a retrospective, single-center investigation conducted at the Fourth Hospital of Hebei Medical University. A total of 379 patients with complete clinical records were enrolled in the Department of Immunology and Rheumatology at the Fourth Hospital of Hebei Medical University from January 2021 to July 2024. Binary logistic regression analysis was employed to identify potential risk factors associated with the development of severe IMH or infection during treatment. Receiver operating characteristic (ROC) curve analysis was further applied to determine the optimal cutoff values for the identified risk factors.ResultsA total of 32 severe IMH patients were analyzed for risk factor association; the Eastern Cooperative Oncology Group performance status (ECOG PS) (p = 0.001) and oral traditional Chinese medicine (TCM) (p < 0.001) were independently associated with the incidence of severe IMH. Based on our experience with these 32 patients, a road map was proposed for the management of severe IMH patients: conventional applications of daily methylprednisolone sodium succinate with dose adjustment for 11 days, a liver biopsy to exclude vanishing bile duct syndrome for steroid-resistant patients, and subsequent plasma exchange (PE). Furthermore, cumulative steroid use was identified as an independent risk factor for concurrent infection with a cutoff value of 1,656 mg (p = 0.024) in severe IMH patients.ConclusionWe investigated the risk factor of severe IMH and provided a feasible treatment roadmap for severe IMH.